Identification of Targets of Transcription Factor WRINKLED1-Like Related to Lipid Biosynthesis From Marine Microalga Dunaliella parva - Shang, Changhua; Pang, Bingbing; Yu, Hongling; Gan, Shanling; Li, Yujia (Frontiers in Marine Science, 2022)
WRINKLED1 (WRI1) is an important transcription factor controlling lipid biosynthesis. To elucidate the function of Dunaliella parva WRI1-like (WRI1-like) (i. e., DpWRI1-like), the targets of DpWRI1-like were identified by chromatin immunoprecipitation sequencing. The results showed that DpWRI1-like regulated many target genes involved in carbohydrate metabolism, lipid metabolism, photosynthesis, and transcription factor. It was proposed that DpWRI1-like participated in a regulatory network controlling lipid biosynthesis. This work laid a good foundation for a deep understanding of the regulatory mechanism of DpWRI1-like in D. parva.